2020
DOI: 10.1088/1757-899x/980/1/012045
|View full text |Cite
|
Sign up to set email alerts
|

Empty fruit bunches, potential fiber source for Indonesian pulp and paper industry

Abstract: Empty fruit bunches (EFB) is one of solid waste from crude palm oil (CPO) mill. It’s about 20-22% from fresh fruit bunches (FFB) or equal to the CPO yield. Indonesian CPO production in 2019 was 51.8 million tons; increased by 9% compared to 2018. So, about 51.8 million tons of EFB was available in 2019. EFB is a potential lignocellulosic material for pulp and paper. The utilization of EFB fibers for papermaking has been studied extensively. The use of EFB for printing and writing papers tends to cause pitch pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
2
0
1
Order By: Relevance
“…The results showed that the average fiber length, fiber diameter, lumen diameter, and cell wall thickness of SPB were 1.34 mm, 20.05 µm, 11.82 µm, and 4.12 µm, respectively. According to the International Association of Wood Anatomy (IAWA) classification, SPB fiber was categorized as moderate (0.9-1.6 mm) [23]. Compared to oil palm bunch and acacia fibers, the fiber length of SPB was longer.…”
Section: Fiber Morphology and Fiber Derivatesmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the average fiber length, fiber diameter, lumen diameter, and cell wall thickness of SPB were 1.34 mm, 20.05 µm, 11.82 µm, and 4.12 µm, respectively. According to the International Association of Wood Anatomy (IAWA) classification, SPB fiber was categorized as moderate (0.9-1.6 mm) [23]. Compared to oil palm bunch and acacia fibers, the fiber length of SPB was longer.…”
Section: Fiber Morphology and Fiber Derivatesmentioning
confidence: 99%
“…This showed that EFB fiber had a high lumen diameter with a thin wall, thereby making it easier to flatten [16]. The Muhlstep ratio and felting power of SPB fibers, namely 64.74 and 68.96, respectively, showed that its fiber was easy to flatten and could form inter-fiber bonding [23]. The coefficient of rigidity and flexibility ratio showed the flexibility degree of the fiber.…”
Section: Fiber Morphology and Fiber Derivatesmentioning
confidence: 99%
“…Faktor utama yang berpengaruh terhadap kekuatan lembaran adalah panjang serat yang digunakan (Indriati et al, 2020). Panjang serat daur ulang OCC sangat beragam tergantung pada sumber dan kualitas OCC yang digunakan.…”
Section: Kualitas Lembaran Laboratoriumunclassified
“…Industri pulp dan kertas merupakan salah satu industri non-migas yang penting dalam mendukung perekonomian nasional [25]. Dalam industri kertas yang menggunakan bahan baku sampah kertas harus melalui dua tahap pengolahan.…”
Section: E Proses Pembuatan Kertas Daur Ulangunclassified